2001
DOI: 10.1161/hc2901.091399
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Atherosclerosis, Aortic Aneurysm Formation, and Ischemic Heart Disease in Apolipoprotein E/Endothelial Nitric Oxide Synthase Double-Knockout Mice

Abstract: Background-To test whether deficiency in endothelial nitric oxide synthase (eNOS) affects atherosclerosis development, we compared lesion formation in apolipoprotein E (apoE)/eNOS-double knockout (DKO) and apoE-knockout (KO) control animals. Methods and Results-After 16 weeks of "Western-type" diet, apoE/eNOS-DKO males and females showed significant increases in lesion area of 93.6% and 59.2% compared with apoE-KO mice. All apoE/eNOS-DKO animals studied developed peripheral coronary arteriosclerosis, associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
430
0
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 569 publications
(457 citation statements)
references
References 36 publications
19
430
0
8
Order By: Relevance
“…Mice eNOS KO mice, 3 apoE KO mice 1 (Jackson Laboratories, Bar Harbor, Maine), and apoE/eNOS DKO mice 5 were all on a C57BL/6 genetic background. Mice were fed a Western-type diet (42% of total calories from fat; 0.15% cholesterol; Harlan-Teklad) for 16 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mice eNOS KO mice, 3 apoE KO mice 1 (Jackson Laboratories, Bar Harbor, Maine), and apoE/eNOS DKO mice 5 were all on a C57BL/6 genetic background. Mice were fed a Western-type diet (42% of total calories from fat; 0.15% cholesterol; Harlan-Teklad) for 16 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…In untreated apoE/eNOS DKO mice after 16 weeks of a Western-type diet, 5 of 12 male mice developed aortic aneurysms; 2 additional mice had aortic dissection. 5 …”
Section: Blood Pressures and Lesion Areas Of Animals Studiedmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Mice lacking eNOS gene have higher blood pressure, insulin resistance, hyperlipidaemia 2 and advanced atherosclerosis. 3 The significant role of NO in the regulation of basal and inducible vasorelaxation suggests that abnormal eNOS activity caused by eNOS mutation may be associated with a number of pathologies such as arterial hypertension or atherosclerosis. 4 Furthermore, it has been shown that NO release and synthesis are decreased in patients with atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%